RADICAL EMPOWERMENT: PRACTICING THE PRINCIPLES IN A COMMUNITY PSYCHOLOGY COURSE - Laura Kati Corlew (PUPIL: International Journal of Teaching, Education and Learning, 2025)
This action research case study explores the implementation of a radical empowerment structure in an undergraduate Community Psychology (CP) course at a rural university in the United States. CP as a field is focused on values such as collective wellbeing, empowerment and citizen participation, collaboration, respect for diversity, and sense of community. The university serves low income, first generation, and other non-traditional students – the focal constituents of much CP research and action. In Spring 2024, the author experimented with radical empowerment in which students designed the syllabus, assignments, weekly agendas, and grading schemes. Students reported working harder in this class than in any other, and the quality of self-assigned weekly homework, reflections, term projects, and presentations was exceptionally high. Students implemented a high level of peer-support, peer-revision, and accountability to each other. The experiment challenged the professor’s understanding of power and trust in education, as well as her role as an educator. Adjustments were made for the second iterations, while maintaining the central tenet of radical empowerment. This design is not appropriate for all subjects, but may be adapted to many full courses or course projects to empower students and cultivate ownership of their education.